PENERAPAN VIDEO PEMBELAJARAN BAGIAN DAN FUNGSI PADA TANAMAN UNTUK KELAS 4 SD DI SD MUHAMMADIYAH 3 DENPASAR: Implementation on Video Tutorial of Plants Parts and Function for 4th Grade Elementary School Students at Muhammadiyah 3 Elementary School Denpasar - Welda Welda; Aniek Suryanti Kusuma; Ayu Manik Dirgayusari; I Nyoman Agus Suarya Putra; I Gusti Agung Indrawan (PUAN INDONESIA, 2023)
Technological advances and the current pandemic situation require SD Muhammadiyah 3 Denpasar to evaluate the current learning system. The current learning system is less effective due to advances in technological developments, as well as the prolonged pandemic situation that has forced the learning system to be carried out online. Students are still confused about participating in online learning, and are often left behind in effective online learning because the gadgets students usually use for online learning are sometimes being used by their parents or other circumstances. Students need a source of literature or other sources of teaching materials that allow students to review the teaching materials after study hours. Therefore, this community service activity is carried out to provide an effective alternative to be applied to students, namely by making animated videos covering natural science subject matter regarding the functions and parts of plants. This community service activity begins with survey and preparation activities, analysis and development of learning videos, and then conducts outreach and training on how to use these learning videos. Based on the results of the training conducted, students and teachers can properly use this learning video as an alternative reference for learning materials.